Heat-conducting insulating sheet with low thermal resistance and high temperature resistance and preparation method of heat-conducting insulating sheet
By using phenylvinyl silicone oil and phenyl hydrogen-containing silicone oil combined with small-particle aluminum oxide and zinc oxide, a low-thermal resistance and high temperature resistance thermal insulation sheet was prepared, which solved the problems of insufficient temperature resistance and high thermal resistance in high temperature environments in existing thermal insulation sheets, and achieved efficient thermal conductivity and high temperature resistance.
Patent Information
- Application Number
- CN202411721145.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The existing thermal insulation sheets have insufficient temperature resistance and high thermal resistance in high temperature environments, making it difficult to meet the needs of PTC heaters under high temperature and high heat generation power.
Phenylvinyl silicone oil and phenyl hydrogen-containing silicone oil are used as main components, and combined with small-particle aluminum oxide and zinc oxide, low-thermal dispersion and calendering composite technology are used to prepare thermally conductive insulating sheets with low thermal resistance and high temperature resistance through high-speed dispersion and calendering composite technology.
The low thermal resistance and high temperature resistance of the thermal insulation sheet are achieved, with a hardness of 80-85 Shore OO, a thermal conductivity coefficient of 3.8-4.2W/mK, a thermal resistance less than 0.18℃*in2/W, a breakdown voltage greater than 9kV, and aging at 250℃ for 1500 hours at a high temperature of 250℃, and a breakdown voltage change less than 15%, and a breakdown voltage change less than 10%.
Smart Images

Figure BDA0005158064380000071 
Figure BDA0005158064380000081 
Figure BDA0005158064380000082
Abstract
Description
Technical Field
[0001] The invention relates to a low-thermal-resistance, high-temperature-resistant heat-conducting insulating sheet and a preparation method thereof, belonging to the technical field of heat-conducting gaskets. Background Art
[0002] At present, PTC heaters are widely used in automotive water heaters. During use, the temperature is maintained above 230°C for a long time, and the voltage is above 2KV during operation, so the requirements for thermally conductive gaskets are very high. The thermally conductive gaskets need to be able to withstand high temperatures for a long time and have good insulation. At the same time, the overall volume of PTC water heaters is getting smaller and smaller, and the number of internal heating elements is relatively reduced, but the overall heating power is required to be higher, which requires the heat transfer effect of thermally conductive gaskets to be better and better. Chinese patent CN218197370U obtains a low thermal resistance thermally conductive insulating sheet by calendering a phase change layer on both sides of the PI film, but the patent does not describe its temperature resistance in detail; Chinese patent CN116092756A discloses a high temperature resistant thermally conductive insulating sheet and its preparation method, but its thermal resistance is only 0.2℃*in 2 / W approximately. Summary of the invention
[0003] The object of the present invention is to provide a low thermal resistance and high temperature resistant thermal conductive insulating sheet and a preparation method thereof, so as to solve the technical problems existing in the prior art.
[0004] To achieve the above objectives, the technical solutions adopted are:
[0005] One of the purposes of the present invention is to provide a low thermal resistance and high temperature resistant thermal conductive insulating sheet, the components of which include, by weight: 100 parts of phenyl vinyl silicone oil, 2-4 parts of phenyl hydrogen silicone oil, 1-4 parts of coupling agent, 6-12 parts of dispersant, 0.1-1 parts of catalyst, 0.2-2 parts of inhibitor, 200-400 parts of aluminum oxide A, 350-550 parts of aluminum oxide B, 450-650 parts of aluminum oxide C and 40-100 parts of zinc oxide.
[0006] On the basis of the above technical solution, the present invention can also be improved as follows:
[0007] Furthermore, the phenyl vinyl silicone oil has a vinyl content of 0.08-0.18 mmoles / gm, a phenyl content of 2-4 mole%, and a viscosity of 1000-1500 cSt.
[0008] The beneficial effect of adopting the above further scheme is that the high temperature resistance of phenyl is much higher than that of the carbon chain structure without benzene. Phenyl vinyl silicone oil is used as the main silicone oil, and phenyl groups are grafted on the side chains, so the high temperature resistance is greatly improved.
[0009] Furthermore, the phenyl hydrogen-containing silicone oil has an active hydrogen content of 2.5-3.5 mmoles / gm, a phenyl content of 6-10 mole%, and a viscosity of 300-600 cSt.
[0010] The beneficial effect of adopting the above further scheme is that the phenyl content of the phenyl hydrogen silicone oil is relatively high, which makes up for its shortcomings of small molecular weight, low viscosity and relatively poor high temperature resistance, thereby further improving the high temperature resistance of the overall resin.
[0011] Furthermore, the coupling agent is a dodecylsilane coupling agent.
[0012] Furthermore, the dispersant is a hydroxyl-containing modified silicone oil.
[0013] Furthermore, the catalyst is a platinum catalyst, wherein the platinum content is 3000 ppm.
[0014] Furthermore, the inhibitor is an alkynol inhibitor.
[0015] Furthermore, the aluminum oxide A is spherical aluminum oxide with a particle size of 0.5-10 um.
[0016] Furthermore, the aluminum oxide B is spherical aluminum oxide with a particle size of 5-15 um.
[0017] Furthermore, the aluminum oxide C is spherical aluminum oxide with a particle size of 30-50 um.
[0018] Furthermore, the particle size of the zinc oxide is 0.01-2 um.
[0019] The beneficial effect of adopting the above further scheme is that by selecting a combination of small-particle aluminum oxide and zinc oxide, the bonding layer thickness (BLT) (the largest powder particle size in the adhesive) of the thermal conductive interface material of the adhesive is relatively small while ensuring the thermal conductivity, thereby reducing thermal resistance.
[0020] The second object of the present invention is to provide a method for preparing the low thermal resistance and high temperature resistant thermally conductive insulating sheet, comprising the following steps:
[0021] (1) adding 100 parts of phenyl vinyl silicone oil, 2-4 parts of phenyl hydrogen silicone oil, 1-4 parts of coupling agent, 6-12 parts of dispersant, 0.1-1 parts of catalyst, 0.2-2 parts of inhibitor, 200-400 parts of aluminum oxide A, and 350-550 parts of aluminum oxide B into a jar, and dispersing them at high speed for 40-80 seconds at a rotation speed of 600-900 rpm; then adding 450-650 parts of aluminum oxide C and 40-100 parts of zinc oxide, and dispersing them at high speed for 40-80 seconds at a rotation speed of 1000-1400 rpm; and finally stirring them at a rotation speed of 300-700 rpm for 20-60 seconds to obtain a pre-material;
[0022] (2) The prepared material obtained in step (1) is calendered and compounded with the PI film, and the first two calendering rollers are used to press the first side of the colloid to a thickness of 0.15-0.19 mm, and then the second side is pressed by the second two calendering rollers to a total thickness of 0.32-0.38 mm, and then vulcanized at 65-100° C. for 45 minutes to obtain a low thermal resistance and high temperature resistant thermal conductive insulating sheet.
[0023] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0024] 1. The present invention adopts phenyl vinyl silicone oil. The high temperature resistance of phenyl is much higher than that of carbon chain structure without benzene. Phenyl vinyl silicone oil is used as the main silicone oil, and phenyl groups are grafted on the side chains to improve the high temperature resistance of the resin body. The phenyl content of phenyl hydrogen silicone oil is relatively high, which makes up for its small molecular weight, low viscosity and relatively poor high temperature resistance, thereby further improving the high temperature resistance of the overall resin; secondly, small particle size aluminum oxide and zinc oxide are selected to match, so that the BLT of the rubber is relatively small while ensuring the thermal conductivity, thereby reducing thermal resistance.
[0025] 2. The low thermal resistance and high temperature resistant thermal insulation sheet prepared by the present invention has a hardness of 80-85 Shore OO, a thermal conductivity of 3.8-4.2 W / mK, and a thermal resistance of less than 0.18℃*in 2 / W, the breakdown voltage is greater than 9kV. After the thermal conductive gasket is placed in a high-temperature 250℃ aging box for 1500h, the thermal resistance change is less than 15%, and the breakdown voltage change is less than 10%. It has been successfully applied in the field of new energy. DETAILED DESCRIPTION
[0026] The principles and features of the present invention are described below in conjunction with examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.
[0027] Example 1
[0028] (1) Add 100 parts of phenyl vinyl silicone oil (vinyl content 0.15 mmoles / gm, phenyl content 3 mole%, viscosity 550 cSt), 3 parts of phenyl hydrogen silicone oil (active hydrogen content 2.8 mmoles / gm, phenyl content 8 mole%, viscosity 400 cSt), 2 parts of coupling agent, 7 parts of dispersant, 0.5 parts of catalyst, 1 part of inhibitor, 280 parts of aluminum oxide A, and 450 parts of aluminum oxide B into a jar, and disperse at high speed for 50 seconds at a rotation speed of 700 rpm; then add 550 parts of aluminum oxide C and 60 parts of zinc oxide, and disperse at high speed for 60 seconds at a rotation speed of 1000 rpm; finally, stir at a rotation speed of 350 rpm for 50 seconds to obtain a pre-material;
[0029] (2) The prepared material obtained in step (1) is calendered and compounded with a 38 μm PI film. The first two calendering rollers are used to press the first side of the colloid to a thickness of 0.17 mm. The second side is then pressed by the second two calendering rollers to a total thickness of 0.37 mm. The calendering rollers are then vulcanized at 100° C. for 45 min to obtain a PI-based double-sided composite silicone sheet with low thermal resistance and high temperature resistance.
[0030] Example 2
[0031] (1) Add 100 parts of phenyl vinyl silicone oil (vinyl content 0.18 mmoles / gm, phenyl content 3 mole%, viscosity 500 cSt), 3.4 parts of phenyl hydrogen silicone oil (active hydrogen content 3 mmoles / gm, phenyl content 9 mole%, viscosity 350 cSt), 4 parts of coupling agent, 10 parts of dispersant, 0.5 parts of catalyst, 1.0 parts of inhibitor, 350 parts of aluminum oxide A, and 450 parts of aluminum oxide B into a jar, and disperse at high speed for 70 seconds at a rotation speed of 600 rpm; then add 650 parts of aluminum oxide C and 80 parts of zinc oxide, and disperse at high speed for 70 seconds at a rotation speed of 1000 rpm; finally, stir at a rotation speed of 350 rpm for 60 seconds to obtain a pre-material;
[0032] (2) The prepared material obtained in step (1) is calendered and compounded with a 38 μm PI film. The first two calendering rollers are used to press the first side of the colloid to a thickness of 0.15 mm. The second side is then pressed by the second two calendering rollers to a total thickness of 0.34 mm. The calendering is then performed at 85° C. for 45 min to obtain a PI-based double-sided composite silicone sheet with low thermal resistance and high temperature resistance.
[0033] Example 3
[0034] (1) Add 100 parts of phenyl vinyl silicone oil (vinyl content 0.15 mmoles / gm, phenyl content 3 mole%, viscosity 550 cSt), 3 parts of phenyl hydrogen silicone oil (active hydrogen content 2.8 mmoles / gm, phenyl content 8 mole%, viscosity 400 cSt), 3 parts of coupling agent, 8 parts of dispersant, 0.6 parts of catalyst, 1.2 parts of inhibitor, 300 parts of aluminum oxide A, and 500 parts of aluminum oxide B into a jar, and disperse at high speed for 70 seconds at a rotation speed of 600 rpm; then add 600 parts of aluminum oxide C and 70 parts of zinc oxide, and disperse at high speed for 70 seconds at a rotation speed of 1000 rpm; finally, stir at a rotation speed of 350 rpm for 60 seconds to obtain a preliminary material;
[0035] (2) The prepared material obtained in step (1) is calendered and compounded with a 38 μm PI film. The first two calendering rollers are used to press the first side of the colloid to a thickness of 0.15 mm. The second side is then pressed by the second two calendering rollers to a total thickness of 0.34 mm. The calendering is then performed at 85° C. for 45 min to obtain a PI-based double-sided composite silicone sheet with low thermal resistance and high temperature resistance.
[0036] Comparative Example 1
[0037] (1) 100 parts of styrene-free silicone oil (vinyl content 0.15 mmoles / gm, viscosity 500 cSt), 3 parts of benzene-free hydrogen-containing silicone oil (active hydrogen content 2.8 mmoles / gm, viscosity 100 cSt), 3 parts of coupling agent, 8 parts of dispersant, 0.6 parts of catalyst, 1.2 parts of inhibitor, 300 parts of aluminum oxide A, and 500 parts of aluminum oxide B were added into a jar, and dispersed at high speed for 70 seconds at a rotation speed of 600 rpm; then 600 parts of aluminum oxide C and 70 parts of zinc oxide were added, and dispersed at high speed for 70 seconds at a rotation speed of 1000 rpm; finally, stirred at a rotation speed of 350 rpm for 60 seconds to obtain a pre-material;
[0038] (2) The prepared material obtained in step (1) is calendered and compounded with a 38 μm PI film. The first two calendering rollers are used to press the first side of the colloid to a thickness of 0.15 mm. The second side is then pressed by the second two calendering rollers to a total thickness of 0.34 mm. The film is then vulcanized at 85° C. for 45 min to obtain a thermally conductive insulating sheet.
[0039] Comparative Example 2
[0040] (1) 100 parts of styrene-free silicone oil (vinyl content 0.15 mmoles / gm, viscosity 500 cSt), 3 parts of phenyl hydrogen silicone oil (active hydrogen content 2.8 mmoles / gm, phenyl content 8 mole%, viscosity 400 cSt), 3 parts of coupling agent, 8 parts of dispersant, 0.6 parts of catalyst, 1.2 parts of inhibitor, 300 parts of aluminum oxide A, and 500 parts of aluminum oxide B were added into a jar, and the mixture was dispersed at high speed for 70 seconds at a rotation speed of 600 rpm; then 600 parts of aluminum oxide C and 70 parts of zinc oxide were added, and the mixture was dispersed at high speed for 70 seconds at a rotation speed of 1000 rpm; finally, the mixture was stirred at a rotation speed of 350 rpm for 60 seconds to obtain a pre-material;
[0041] (2) The prepared material obtained in step (1) is calendered and compounded with a 38 μm PI film. The first two calendering rollers are used to press the first side of the colloid to a thickness of 0.15 mm. The second side is then pressed by the second two calendering rollers to a total thickness of 0.34 mm. The film is then vulcanized at 85° C. for 45 min to obtain a thermally conductive insulating sheet.
[0042] Comparative Example 3
[0043] (1) 100 parts of phenyl vinyl silicone oil (vinyl content 0.15 mmoles / gm, phenyl content 3 mole%, viscosity 550 cSt), 3 parts of benzene-free hydrogen-containing silicone oil (active hydrogen content 2.8 mmoles / gm, viscosity 100 cSt), 3 parts of coupling agent, 8 parts of dispersant, 0.6 parts of catalyst, 1.2 parts of inhibitor, 300 parts of aluminum oxide A, and 500 parts of aluminum oxide B were added into a jar and dispersed at high speed for 70 seconds at a rotation speed of 600 rpm; then, 600 parts of aluminum oxide C and 70 parts of zinc oxide were added and dispersed at high speed for 70 seconds at a rotation speed of 1000 rpm; finally, stirred at a rotation speed of 350 rpm for 60 seconds to obtain a pre-material;
[0044] (2) The prepared material obtained in step (1) is calendered and compounded with a 38 μm PI film. The first two calendering rollers are used to press the first side of the colloid to a thickness of 0.15 mm. The second side is then pressed by the second two calendering rollers to a total thickness of 0.34 mm. The film is then vulcanized at 85° C. for 45 min to obtain a thermally conductive insulating sheet.
[0045] Comparative Example 4
[0046] 100 parts of phenyl vinyl silicone oil (vinyl content 0.15 mmoles / gm, phenyl content 8 mole%, viscosity 650 cSt), 3 parts of phenyl hydrogen silicone oil (active hydrogen content 2.8 mmoles / gm, phenyl content 12 mole%, viscosity 500 cSt), 2 parts of coupling agent, 7 parts of dispersant, 0.5 parts of catalyst, 1 part of inhibitor, 280 parts of aluminum oxide A, and 450 parts of aluminum oxide B were added into a jar, and dispersed at high speed for 50 seconds at a speed of 700 rpm; then 550 parts of aluminum oxide C and 60 parts of zinc oxide were added, and dispersed at high speed for 60 seconds at a speed of 1000 rpm; finally, stirred at a speed of 350 rpm for 50 seconds. Due to the high phenyl content, the powder could not be filled, and calendering and compounding were even more impossible.
[0047] Comparative Example 5
[0048] (1) Add 100 parts of phenyl vinyl silicone oil (vinyl content 0.15 mmoles / gm, phenyl content 3 mole%, viscosity 550 cSt), 3 parts of phenyl hydrogen silicone oil (active hydrogen content 2.8 mmoles / gm, phenyl content 8 mole%, viscosity 400 cSt), 3 parts of coupling agent, 8 parts of dispersant, 0.6 parts of catalyst, 1.2 parts of inhibitor, 100 parts of aluminum oxide A, and 500 parts of aluminum oxide B into a jar, and disperse at high speed for 70 seconds at a rotation speed of 600 rpm; then add 800 parts of aluminum oxide C and 50 parts of zinc oxide, and disperse at high speed for 70 seconds at a rotation speed of 1000 rpm; finally, stir at a rotation speed of 350 rpm for 60 seconds to obtain a preliminary material;
[0049] (2) The prepared material obtained in step (1) is calendered and compounded with a 38 μm PI film. The first two calendering rollers are used to press the first side of the colloid to a thickness of 0.15 mm. The second side is then pressed by the second two calendering rollers to a total thickness of 0.34 mm. The film is then vulcanized at 85° C. for 45 min to obtain a thermally conductive insulating sheet.
[0050] Comparative Example 6
[0051] (1) Add 100 parts of phenyl vinyl silicone oil (vinyl content 0.15 mmoles / gm, phenyl content 3 mole%, viscosity 550 cSt), 3 parts of phenyl hydrogen silicone oil (active hydrogen content 2.8 mmoles / gm, phenyl content 8 mole%, viscosity 400 cSt), 3 parts of coupling agent, 8 parts of dispersant, 0.6 parts of catalyst, 1.2 parts of inhibitor, 150 parts of aluminum oxide A, and 600 parts of aluminum oxide B into a jar, and disperse at high speed for 70 seconds at a rotation speed of 600 rpm; then add 400 parts of aluminum oxide C and 110 parts of zinc oxide, and disperse at high speed for 70 seconds at a rotation speed of 1000 rpm; finally, stir at a rotation speed of 350 rpm for 60 seconds to obtain a preliminary material;
[0052] (2) The prepared material obtained in step (1) is calendered and compounded with a 38 μm PI film. The first two calendering rollers are used to press the first side of the colloid to a thickness of 0.15 mm. The second side is then pressed by the second two calendering rollers to a total thickness of 0.34 mm. The film is then vulcanized at 85° C. for 45 min to obtain a thermally conductive insulating sheet.
[0053] In the above embodiments and comparative examples, the coupling agent is dodecylsilane coupling agent; the dispersant is hydroxyl-containing modified silicone oil, brand: DA30, manufacturer: Anbi Ya Special Silicone Co., Ltd.; the catalyst is a platinum catalyst, wherein the platinum content is 3000ppm; the inhibitor is an acetylenic alcohol inhibitor, specifically an ethynyl cyclohexanol inhibitor.
[0054] The thermally conductive pads obtained in Examples 1-3 and Comparative Examples 1-6 were subjected to performance tests:
[0055] (1) Hardness test: Tested according to ASTM D2240 standard;
[0056] (2) Thermal conductivity test: Tested in accordance with ISO22007-2.2 standard;
[0057] (3) Thermal resistance test: Tested according to ASTM D5470 standard;
[0058] (4) Breakdown voltage test: Tested in accordance with ASTM D149 standard;
[0059] The test results are shown in Table 1 below:
[0060] Table 1. Performance test results of thermal insulation sheet
[0061]
[0062]
[0063] The performance test results after high temperature 250℃ aging for 1500h are shown in Table 2 below:
[0064] Table 2. Performance test results of thermal insulation sheet after aging at 250℃ for 1500h
[0065]
[0066] From the test results of Examples 1-3 and Comparative Examples 1-6, it can be seen that the hardness of the thermally conductive pads prepared in Examples 1-3 is 80-85 Shore OO, the thermal conductivity is 3.8-4.2 W / mK, and the thermal resistance is less than 0.18℃*in 2 / W, the breakdown voltage is greater than 9kV, after aging at high temperature of 250℃ for 1500h, there is no cracking and powdering on the surface, and the thermal resistance change is less than 15%, and the breakdown voltage change rate is less than 10%; the hardness of the thermal conductive gaskets prepared in comparative examples 1-6 is 75-85Shore OO, and the thermal resistance of comparative examples 1-3 is also less than 0.18℃*in 2 / W, the breakdown voltage is also greater than 9kV, but after aging at high temperature of 250℃ for 1500h, the colloid surface cracks and delaminates with the PI film, and the thermal resistance and breakdown voltage also change significantly. In comparative example 4, due to the high phenyl content in the silicone oil, the powder cannot be filled. The initial thermal resistance of comparative examples 5-6 is larger, greater than 0.18℃*in 2 / W.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A low thermal resistance and high temperature resistant thermal conductive insulating sheet, characterized in that: The invention comprises, by weight: 100 parts of phenyl vinyl silicone oil, 2-4 parts of phenyl hydrogen silicone oil, 1-4 parts of coupling agent, 6-12 parts of dispersant, 0.1-1 parts of catalyst, 0.2-2 parts of inhibitor, 200-400 parts of aluminum oxide A, 350-550 parts of aluminum oxide B, 450-650 parts of aluminum oxide C and 40-100 parts of zinc oxide.
2. The low thermal resistance and high temperature resistant thermal conductive insulating sheet according to claim 1, characterized in that: The phenyl vinyl silicone oil has a vinyl content of 0.08-0.18 mmoles / gm, a phenyl content of 2-4 mole%, and a viscosity of 1000-1500 cSt.
3. The low thermal resistance and high temperature resistant thermal conductive insulating sheet according to claim 1, characterized in that: The active hydrogen content of the phenyl hydrogen-containing silicone oil is 2.5-3.5 mmoles / gm, the phenyl content is 6-10 mole%, and the viscosity is 300-600 cSt.
4. The low thermal resistance and high temperature resistant thermal conductive insulating sheet according to claim 1, characterized in that: The coupling agent is a dodecylsilane coupling agent; the dispersant is a hydroxyl-containing modified silicone oil; the catalyst is a platinum catalyst; and the inhibitor is an acetyl alcohol inhibitor.
5. The low thermal resistance and high temperature resistant thermally conductive insulating sheet according to claim 1, characterized in that: The aluminum oxide A is spherical aluminum oxide with a particle size of 0.5-10 um.
6. The low thermal resistance and high temperature resistant thermal conductive insulating sheet according to claim 1, characterized in that: The aluminum oxide B is spherical aluminum oxide with a particle size of 5-15 um.
7. The low thermal resistance and high temperature resistant thermally conductive insulating sheet according to claim 1, characterized in that: The aluminum oxide C is spherical aluminum oxide with a particle size of 30-50 um.
8. The low thermal resistance and high temperature resistant thermal conductive insulating sheet according to claim 1, characterized in that: The particle size of the zinc oxide is 0.01-2 um.
9. A method for preparing a low thermal resistance and high temperature resistant thermally conductive insulating sheet according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) adding 100 parts of phenyl vinyl silicone oil, 2-4 parts of phenyl hydrogen silicone oil, 1-4 parts of coupling agent, 6-12 parts of dispersant, 0.1-1 parts of catalyst, 0.2-2 parts of inhibitor, 200-400 parts of aluminum oxide A, and 350-550 parts of aluminum oxide B into a jar, and dispersing at high speed for 40-80 seconds at a rotation speed of 600-900 rpm; then adding 450-650 parts of aluminum oxide C and 40-100 parts of zinc oxide, and dispersing at high speed for 40-80 seconds at a rotation speed of 1000-1400 rpm; and finally stirring at a rotation speed of 300-700 rpm for 20-60 seconds to obtain a pre-material; (2) The prepared material obtained in step (1) is calendered and compounded with the PI film, and the first two calendering rollers are used to press the first side of the colloid to a thickness of 0.15-0.19 mm, and then the second side is pressed by the second two calendering rollers to a total thickness of 0.32-0.38 mm, and then vulcanized at 65-100° C. to obtain a low thermal resistance and high temperature resistant thermal conductive insulating sheet.
Citation Information
Patent Citations
Preparation method of high-temperature-resistant heat-conducting insulating sheet and high-temperature-resistant heat-conducting insulating sheet
CN116092756A
Low-thermal-resistance heat-conducting insulating film
CN218197370U